Should We Give All We Have to Live On? A Theological Proposal for the Ethics of Generosity - Blosser, Andrew (Heythrop journal, 2022)
Recent ethical literature has called attention to subtle yet profound difficulties in determining what types of generosity are moral, and what situations call for generosity. This article contributes to this discussion by advancing a perspective drawn from Christian theology, according to which philanthropic endeavours must follow a downwards trajectory, modelled on God’s self-donation. Once this model is understood, potentially problematic rhetorical frameworks of generosity—such as that of Anselm of Canterbury—can be identified. This article further argues that the downwards trajectory of generosity has important implications for institutions that use philanthropic rhetoric in their fundraising, as well as for philosophers seeking to establish conditions for ethical generosity.